Moral Transformation in the Process of the First and Final Revelations in the Qur'an - Dinda Ramdani; Siti Sanah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The decline of morality in modern life shows the need for a reassessment of the noble values contained in the Qur'an, especially in the first and last revelations that brought great changes to the Jahili Arab society. This research aims to analyze the moral values contained in the process of the first and last revelation in the Qur'an. This research uses a qualitative method with a library research approach with the main sources being books, journals, and tafsir books. The results showed that the first revelation initiated moral change by emphasizing the importance of learning and spirituality, while the last revelation perfected the principles of justice and balance in social and legal systems. In conclusion, the moral values of these two revelations remain relevant as guidelines to face moral challenges in the modern era.